Social – Philosophic Analyses of The Concept “Culture” - Saira, Rakhipova; Aigan, Berikova; Venera, Yenseyeva; Sholpan, Zhaukumova; Dinara, Zhamaubayeva (International Journal of Psychosocial Rehabilitation, 2020)
One of the main categories of philosophy is the concept of culture. At the same time, the concept in modern science has not yet received a consistent understanding and adequate metalanguage description. The methods and techniques of lcognitive analysis of concepts are not well-established, they have not found the optimal solution to the problem of combining structural-semantic and cognitive procedures, diachronic and synchronous aspects, the verbal existence of concepts, their comparative study in the framework of both one and different ethnic language continuums. This largely determines the choice of the topic of the research.